PENGARUH KUALITAS PELAYANAN PETUGAS AVSEC DI SECURITY CHECK POINT (SCP) TERHADAP KEPUASAN PENUMPANG DI BANDAR UDARA SULTAN BABULLAH TERNATE - M Ibrahim, Ali Yusran; Hodi, Hodi (Relawan Jurnal Indonesia, 2022)
Aviation Security (AVSEC) is a work unit formed by PT. Angkasa Pura in fulfilling international and national regulations as a manager and provider of airport security services must have the required license according to the position. The quality of security services provided by security officers or Aviation Security (AVSEC) at the Security Check Point (SCP) unit at Sultan Babullah Airport Ternate is very important for passengers. the researcher got information from seniors who had already carried out On Job Training (OJT) where there were some passengers who complained about the service during the inspection. Therefore, the researcher aims to find out whether there is an influence on the quality of service of avsec officers at the security check point on passenger satisfaction and also to find out how much influence the quality of service of avsec officers at the security check point has on passenger satisfaction at Sultan Babullah Airport, Ternate This study uses quantitative data. The data used in this study were taken from primary data based on questionnaires distributed to passengers at Sultan Babullah Airport Ternate for the period February 2022. With a total of 96 people, the data analysis technique used was simple linear regression analysis, T test, coefficient of determination and normality test. The results showed that Ho was rejected and Ha was accepted, which means that there is an influence of service quality for Avsec Officers at Security Check Point (SCP) on Passenger Satisfaction at Sultan Babullah Airport, Ternate. The T test results show tcount = 15.212> ttable value = 1.985. The results of the Coefficient of Determination test which show how much influence the service quality variable (X) has on the passenger satisfaction variable (Y) it is known that the determination coefficient value is 71.1%, which means that the service quality variable (X) contributes 71.1% to the passenger satisfaction variable. (Y), while the remaining 28.9% was caused by other factors not examined by the researcher. Keywords: Quality of Service, Passenger Satisfaction, Sultan Babullah Ternate